T-lymphocytes FoxP3+ and their interconnection with the severity of coronary atherosclerosis in patients with coronary artery disease and diabetes mellitus type 2: a pilot study - I. V. Kologrivova; O. A. Koshelskaya; T. E. Suslova; O. A. Kharitonova; O. A. Trubacheva; E. S. Kravchenko; A. A. Dmitriukov (Сахарный диабет)
BACKGROUND: One of the common pathogenic links of diabetes mellitus type 2 (T2DM) and coronary artery disease (CAD) is chronic low-grade inflammation, restricted by FoxP3+ T-regulatory lymphocytes.AIM: To investigate the numbers of FoxP3+CD25hi and FoxP3+CD25lo T-lymphocytes, the subcellular localization of FoxP3 in them, and the production of the main cytokines in relation to clinical and metabolic parameters in patients with association of CAD and T2DM.MATERIALS AND METHODS: An observational single-center single-stage comparative study was conducted. The severity of atherosclerosis was assessed by calculating the Gensini Score index after coronary angiography. Absolute numbers and frequencies of CD4+CD25hiFoxP3+ and CD4+CD25loFoxP3+ T-lymphocytes were assessed in peripheral blood by flow cytometry. Imaging flow cytometry was used to determine the degree of FoxP3 translocation to the cell’s nucleus. Concentration of cytokines in blood serum and supernatants of mononuclear leukocytes’ cultures was determined by the multiplex analysis.RESULTS: We recruited 57 patients with chronic CAD. Of these, T2DM was diagnosed in 22 patients. In patients with CAD and T2DM, the absolute numbers and frequencies of FoxP3+CD25lo cells were increased compared to patients with CAD without diabetes (1.15 (0.98; 1.73) vs. 0.96 (0.60; 1.15)% (р=0.046); 1.48 (1.05; 1.97) vs. 1.07 (0.71; 1.42) x107/L (р=0.025)). Patients with T2DM also had a higher level of translocation of FoxP3 to the nucleus of FoxP3+CD25lo cells (92.0 (86.4; 95.0) vs. 88.7 (80.0; 91.4)%, р=0.040) and increased concentration of the chemokine CCL22 both in blood serum (912 (828; 1061) vs. 669 (585; 738) pg/mL, р=0.022) and supernatants of LPS-stimulated mononuclear leukocyte cultures (1189 (851; 1310) vs. 539 (437; 949) pg/mL, р=0.038), which correlated with the presence of CD4+CD25hiFoxP3+ cells (Rs=0.587; p=0.044) and the triglyceride/glucose index (Rs=0.587; p=0.044). The identified changes were most pronounced in patients with moderately elevated values on the Gensini Score (17–45 points).CONCLUSION: We are the first to show association between the numbers of FoxP3+CD25lo-lymphocytes in peripheral blood and an increase in the nuclear translocation of FoxP3 in them with the severity of atherosclerosis in patients with association of CAD and T2DM. These data justify the necessity of the further investigation of the diagnostic significance of FoxP3+CD25lo-cells as biomarkers of tissue inflammation.